Current concepts in chronic inflammatory diseases: Interactions between microbes, cellular metabolism, and inflammation - Garn, Holger; Bahn, Sabine; Baune, Bernhard T.; Binder, Elisabeth B.; Bisgaard, Hans; Chatila, Talal A.; Chavakis, Triantafyllos; Culmsee, Carsten; Dannlowski, Udo; Gay, Steffen; Gern, James; Haahtela, Tari; et al. (Journal of Allergy and Clinical Immunology, 2016)
Recent research indicates that chronic inflammatory diseases, including allergies and autoimmune and neuropsychiatric diseases, share common pathways of cellular and molecular dysregulation. It was the aim of the International von-Behring-Röntgen Symposium (October 16-18, 2014, in Marburg, Germany) to discuss recent developments in this field. These include a concept of biodiversity; the contribution of urbanization, lifestyle factors, and nutrition (eg, vitamin D); and new mechanisms of metabolic and immune dysregulation, such as extracellular and intracellular RNAs and cellular and mitochondrial stress. Epigenetic mechanisms contribute further to altered gene expression and therefore to the development of chronic inflammation. These novel findings provide the foundation for further development of preventive and therapeutic strategies.
EVALuna2:2160